Overshadowing depends on cue and reinforcement sensitivity but not schizotypy - Pickett, Clare; Cassaday, Helen J.; Bibby, Peter A. (Elsevier, 2017)
There is evidence for impaired selective learning mechanisms in individuals high in schizotypy. Overshadowing provides a direct test of selective learning based on cue salience and has previously been reported to be impaired in relation to schizotypy scores. The present study tested for overshadowing using food allergy and Lego construction task variants. Both variants used the same number of conditioned stimulus (CS) cues and the same number of learning trials. CS cues were trained in compound pairs or in isolation and overshadowing was subsequently tested on trials followed by negative versus positive outcomes. Participants also completed the O-LIFE to measure schizotypy and BIS-BAS scales to measure reinforcement sensitivity. Learning was demonstrated for both cue variants; however overshadowing emerged only in the Lego variant and only on the trials followed by the negative outcome. Contrary to expectations, there was no evidence for any relationship between overshadowing and O-LIFE scores. However, there was evidence of a positive relationship between overshadowing and BAS-Drive as well as a negative relationship with BIS-Anxiety, for the trials followed by the positive outcome in the food allergy variant. These results suggest that the development of overshadowing depends on cue and reinforcement sensitivity, but not necessarily on schizotypy.